Impact of corruption on financial development in middle income countries - Haw, Meng Jie (2012)
Research always suggests that a country able to experience a remarkable economic growth through developing the financial institution. Although scholars had suggested few major factors that determine financial development, yet there are still countries with different financial development level. This study focuses on the impact of corruption on financial development in middle income countries. A further investigation about the existence of corruption threshold has also been carried out using threshold regression by Hansen (2000). By using cross sectional Ordinary Least Squares method, corruption is found to be highly correlated with financial development, especially in the banking sector. Besides, evidence shows that there is a threshold level of corruption; a highly corrupt country are more likely to further develop its financial sector by fighting corruption. The finding supports the view that state that corruption harms financial development.